Synthesis, characterization and corrosion inhibition studies of benzoyl thiourea derivatives / Noor Khadijah Mustafa Kamal - Mustafa Kamal, Noor Khadijah (2017)
A series of benzoylthiourea compounds, namely JV-phenyl-iV '-benzoylthiourea (Bl) and its methoxy (B2), nitro (B3) and chloro (B4) derivatives were successfully synthesized from the reaction of benxoyl chloride with amine derivatives in acetone reflux. The effectiveness of these compounds as corrosion inhibitor on mild steel in 1.0 M H2SO4 solution was measured using weight loss method, linear polarization resistance (LPR) technique and electrochemical impedance spectroscopy (EIS). The inhibition efficiency (IE%) was affected by the presence of substituent such as methoxy, nitro and chloro. Compound B2 that contain methoxy substituent has the highest IE% which is 90.59%. The order of the effectiveness of the compounds as corrosion inhibitors is B2>B1>B4>B3. All four compounds are mixed-type inhibitors and the inhibition of these compounds obeyed the Langmuir adsorption isotherm.